Restoration for community-wide benefits through inclusive Restoration Co-Design (ReCoDe) and testing: a draft protocol - Sircely, Jason A; Bullock, Renee (International Livestock Research Institute, 2025)
This protocol provides a method for inclusive Restoration Co-Design (ReCoDe) that engages a wide array of stakeholders to directly influence large-scale restoration in community grazing lands. The overall idea is to solicit the viewpoints of different groups of stakeholders in a community, and to incorporate these various perspectives in the process of creating, testing, and expanding land restoration in a particular community. Here, community stakeholder groups include producers, local institutions, and land managers, across differences in terms of gender, age, and other factors such as levels of education, wealth, or other forms of relative privilege or disprivilege as may be found in almost any community around the world.